Merging Transition-Metal Catalysis with Photoredox Catalysis: An Environmentally Friendly Strategy for C–H Functionalization - Zhou, Wen-Jun; Zhang, Yi-Han; Gui, Yong-Yuan; Sun, Liang; Yu, Da-Gang (Synthesis, 2018)
Transition-metal-catalyzed C–H functionalization is already a useful tool in organic synthesis, whilst the rapid development of photoredox catalysis provides new pathways for C–H functionalization with high selectivity and efficiency under mild reaction conditions. In this review, recent advances in C–H functionalization through merging transition-metal catalysis with photoredox catalysis are discussed.1 Introduction2 Merging Nickel Catalysis with Photoredox Catalysis3 Merging Palladium Catalysis with Photoredox Catalysis4 Merging Cobalt Catalysis with Photoredox Catalysis5 Merging Photoredox Catalysis with Other Transition-Metal Catalysis6 Conclusions
Keywords: transition-metal catalysis; photoredox catalysis; C–H functionalization; selectivity; mild reaction conditions